PENGARUH KEMASAN TERHADAP AKTIVITAS ANTI BAKTERI SUSPENSI ERITROMISIN SETELAH PENYINARAN DENGAN SINAR MATAHARI LANGSUNG - Nurul Hidayati (Jurnal Ilmiah Manuntung, 2016)
Erythromycin is a type of antibiotic medication. The drug is unstable when in the water because it can undergo hydrolysis process. Fortunately, it can be prevented by making dry syrup dosage form. In addition to hydrolysis, erythromycin can also have photolysis. For preventing the reaction, it can be done by packing the medication in an opaque and tightly closed container. This research was conducted to determine the effect of packaging on the stability of erythromycin suspension that has been exposed to direct sunlight within a period. The research was done by exposing erythromycin suspension, which was packed with three kinds of color packaging namely brown, translucent, and opaque, for 30 minutes, 60 minutes, 90 minutes and 120 minutes, then continued by a microbiological test with a diffusion method to determine the activity of erythromycin against Staphylococcus Aureus. The results of the research showed the existence of diameter of barrier areas around the spots that were given a test solution. It means that the test solution has antibiotic activity against bacteria. Preparations packaged in brown color have higher inhibition when compared with the opaque and translucent. It shows that the erythromycin suspension packaged in brown colors was more efficient in stabilizing the preparation